Empirical evaluation of mixed approach in adaptive hypermedia learning system - Haron, Norreen (2006)
Research on learning has shown that student learn more effectively when taught with methods that suits to their learning style. Regarding to the problem, an adaptive hypermedia learning system that exploit a mixed approach has been developed. The mixed approach comprise of 2 approaches; computer intelligence (fuzzy logic approach) and personality factor (MBTI approach) that use to individualize the learning material structure. It aims to utilize the learning characteristics and provide a personalized learning environment that exploit pedagogical model and fuzzy logic techniques. The learning material consists of 4 structures; 1) theory, 2) examples 3) exercises and 4) activities. The pedagogical model and learning characteristics are based on the student’s personality factor (Myers-Briggs Type Indicator (MBTI)), whilst the fuzzy logic techniques are used to classify the structure of learning material which is based on student’s personality factors. This paper tends to exemplify the evaluation process for mixed approach. The evaluation is comprised of two methods; usability and utility which is both of the methods are referring to the learnability factor, efficiency factor, satisfaction factor and accuracy factor. The system has been tested by 44 students from Faculty of Computer Science. Most of the participants give good response and the results from the evaluation have been very satisfactory.